The Mexican consensus on non-cardiac chest pain - Gómez Escudero, O.; Coss Adame, E.; Amieva Balmori, M.; Carmona Sánchez, R.I.; Remes Troche, José M.; Abreu Abreu, A.T.; Cerda Contreras, E.; Gómez Castaños, P.C.; González Martínez, M.A.; Huerta Iga, F.M.; Ibarra Palomino, J.; Icaza Chávez, M. E.; et al. (Asociación Mexicana de Gastroenterología, 2019)
Non-cardiac chest pain is defined as a clinical syndrome characterized by retrosternal pain similar to that of angina pectoris, but of non-cardiac origin and produced by esophageal, musculoskeletal, pulmonary, or psychiatric diseases. Aim: To present a consensus review based on evidence regarding the definition, epidemiology,pathophysiology, and diagnosis of non-cardiac chest pain, as well as the therapeutic options for those patients. Methods Three general coordinators carried out a literature review of all articles published in english and spanish on the theme and formulated 38 initial statements, dividing them into 3 main categories: 1) definitions, epidemiology, and pathophysiology, 2) diagnosis, and 3) treatment.The statements underwent 3 rounds of voting, utilizing the Delphi system. The final statements were those that reached > 75% agreement, and they were rated utilizing the GRADE system. Results and conclusions The final consensus included 29 statements. All patients presenting with chest pain should initially be evaluated by a cardiologist. The most common cause of non-cardiac chest pain is gastroesophageal reflux disease. If there are no alarm symptoms, the initial approach should be a therapeutic trial with a proton pump inhibitor for 2-4 weeks. If dysphagia or alarm symptoms are present, endoscopy is recommended. High-resolution manometry is the best method for ruling out spastic motor disorders and achalasia and pH monitoring aids in demonstrating abnormal esophageal acid exposure. Treatment should be directed at the pathophysiologic mechanism. It can include proton pump inhibitors, neuromodulators and/or smooth muscle relaxants, psychologic intervention and/or cognitive therapy, and occasionally surgery or endoscopic therapy.